Impact of Taxes, Transfers, and Subsidies on Income Distributionand Poverty in Argentina - Rossignolo, Dario (Economia, 2023)
This study evaluates the impact of direct and indirect taxes, as well as public expenditure on transfers (monetary and in-kind, economic subsidies, healthcare, and education), on income distribution and poverty in Argentina. It utilizes a standard fiscal incidence analysis and combines data from the Permanent Household Survey (EPH) and the National Household Expenditure Survey (ENGHo). The findings indicate that fiscal policy has been a powerful instrument in reducing inequality and poverty. However, unusually high levels of public spending could potentially render the programs unsustainable.